Розв’яжіть рівняння (2х -1) (4х ^ 2 + 2х + 1) = 23 + 4х (2х ^ 2-3)

Розв'яжіть рівняння (2х -1) (4х ^ 2 + 2х + 1) = 23 + 4х (2х ^ 2-3)

  • На фотке рішення. Відповідь: х = 2
Розв'яжіть рівняння (2х -1) (4х ^ 2 + 2х + 1) = 23 + 4х (2х ^ 2-3)

  • (2x-1) (4x + 2x +1) = 23 + 4x (2x -3);
    (2x) -1 = 23 + 8x -12x;
    8x - 1 = 23 + 8x -12x;
    12x = 24;
    x = 2 .
  • Понравилась статья? Поделиться с друзьями:
    Добавить комментарий

    + 52 = 53

    ;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!: